2015
DOI: 10.4085/1062-6050-49.6.06
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Biomechanics and Self-Reported Foot-Strike Patterns Among Runners in Traditional and Minimalist Shoes

Abstract: Context:The injury incidence rate among runners is approximately 50%. Some individuals have advocated using an anterior-foot-strike pattern to reduce ground reaction forces and injury rates that they attribute to a rear-foot-strike pattern. The proportion of minimalist shoe wearers who adopt an anterior-foot-strike pattern remains unclear.Objective: To evaluate the accuracy of self-reported footstrike patterns, compare negative ankle-and knee-joint angular work among runners using different foot-strike pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…These findings are expected based on loading patterns of the lower extremity while utilizing a NRFS pattern . Goss et al observed that there is increased negative work of the plantar flexors in NRFS runners compared to RFS runners . This may explain the large percentage of self‐reported ankle and leg injuries in this group.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…These findings are expected based on loading patterns of the lower extremity while utilizing a NRFS pattern . Goss et al observed that there is increased negative work of the plantar flexors in NRFS runners compared to RFS runners . This may explain the large percentage of self‐reported ankle and leg injuries in this group.…”
Section: Discussionmentioning
confidence: 68%
“…The most common location for injuries in the NRFS runners was the foot (n = 12), ankle (n = 8), and leg (n = 12), accounting for 75% of the injuries in this group. These findings are expected based on loading patterns of the lower extremity while utilizing a NRFS pattern . Goss et al observed that there is increased negative work of the plantar flexors in NRFS runners compared to RFS runners .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Over the last decades, many running shoe features such as motion control, enhanced cushioning or elevated heel have been developed to improve comfort and protect against runninginduced repetitive overload. [1][2][3] Indeed, some of these shoe technologies were recently associated with the risk of sustaining a running-related injury in retrospective 4 as well as in prospective cohort studies. [5][6][7] Therefore, identifying biomechanical adaptations associated with these technologies is essential to understand the mechanism of any protective effects.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Alterations in SR have consistently demonstrated the ability to reduce lower extremity loads associated with injury development to include; average vertical loading rate (AVLR), 10 shock attenuation, 11 and energy absorbed at the hip, knee, and ankle joints during running. 6 Individuals recovering from anterior exertional compartment syndrome, 12,13 tibial stress fracture, 14 anterior shin pain, 15 and patellofemoral pain 16,17 have reported reductions in running pain after gait retraining to increase their SR. By increasing one's preferred SR by 10% or greater (assuming a constant speed), reduced impact load on the body can be achieved. 6,10 A runner's FSP and the resulting loading properties may also be a principal factor in lower extremity injury.…”
Section: Introductionmentioning
confidence: 99%